Malay Local Wisdom Values in Learning at Elementary Schools - Sinthya, Vany; Ramadan, Zaka Hadikusuma (Universitas Pendidikan Ganesha, 2021)
Local wisdom is cultural wisdom that is understood as the result of wise thinking, full of wisdom, has value and becomes a role model for the community. Malay culture is very diverse from spoken to written. With the thick Malay culture, it does not mean that the culture is not influenced from outside. The purpose of this study was to analyze the implementation of Malay local wisdom values in learning in elementary schools. The researcher used a qualitative approach with a descriptive method. The subjects of this study were 1 principal, 7 teachers and 16 students. Researchers made observations starting from grades 1 to 6 with representatives of 6 classes. Money data collection techniques used by researchers in the form of interviews, observation, documentation. The data analysis technique used is descriptive qualitative. The results showed that the value of Malay local wisdom was implemented well in schools and in every lesson. There are five values of local Malay wisdom that are applied in learning, namely religious values, peace-loving values, mutual cooperation values, tolerance values, and environmental care values.